Impression Management: A Research In Insurance Sector - Rüzgar, Nılüfer (My University, 2025)
Impression management is a concept that expresses how individuals present their characters and their behaviors in line with the goal they want to achieve. When considered in the organizational context, impression management tactics can often be used by employees who want to gain certain privileges such as promotions, raises, appreciation and resource use, and by managers who want to have an impact on their employees that will motivate them to work harder and increase performance. In this sense, the aim of this research is to reveal insurance sector employees’ attitudes towards impression management. In the scope of the research, demographic questions and Impression Management Scale (Bozkurt Yıldırım, 2019) are prepared as a survey form and the surveys were delivered to the employees via e-mail. 134 employees participated in the research and the data was analysed via SPSS 22.0 programme. Findings reveal that, there is a statistically significant difference (p <0.05) between gender, age and experience characteristics and all dimensions of the scale (camouflage, curry favor, protect image, intimidation). In addition, findings also reveal that there is not a statistically significant difference (p >0.05) between marital status characteristic and all dimensions of the scale (camouflage, curry favor, protect image, intimidation).
Keywords: Impression management; tactics; impression; insurance agencies; privileges